Electrical safety-related work practices (Burlington, MA : Jone and Bartlett Learning, 2014)
Chapters explore calculations required to comply with NFPA 70E, and techniques that can be applied to significantly reduce or eliminate electrical hazards.
Machine generated contents note: ch. 1 Electrical Safety Culture -- Introduction -- Safety Culture -- Hazard Awareness and Recognition -- Historical Methods for Testing Voltage -- Cardiopulmonary Resuscitation: Accepted Practice in the Early 1900s -- Occupational Safety and Health Administration (OSHA) 29 CFR 1910.333(a)(1) -- Trauma Following Electrical Events -- Arcing Faults Present Multiple Hazards -- Recognizing Limitations of PPE -- Understanding Requirements -- Decisions -- Appropriate Priorities -- Training and Personal Responsibility -- Costs of Energized Work Versus Shutting Down -- Time Pressure -- Employee Qualification -- Implementation Choices -- Summary -- Introduction to the NIOSH FACE Program -- ch. 2 Electrical Hazard Awareness -- Introduction -- Workplace Hazards -- Electrical Shock -- Skin Resistance -- Extent of Injury -- Prevention -- Arcing Faults: Arc Flash and Arc Blast -- Arcing Fault Basics -- Arc Flash -- Arc Blast -- How Arcing Faults Can Affect Humans -- Staged Arc-Flash Tests -- The Role of Overcurrent Protective Devices in Electrical Safety -- Summary -- ch. 3 OSHA Considerations -- Introduction -- OSHA: History, Application, Enforcement, and Responsibility -- History -- Application -- Enforcement -- Responsibility -- The OSH Act and OSHA Standards and Regulations -- Employer and Employee Duties -- Standards and Regulations -- Safety and Health Regulations for Construction -- General Safety and Health Provisions -- Personal Protective and Life-Saving Equipment -- Electrical -- Occupational Safety and Health Standards -- General -- Personal Protective Equipment -- The Control of Hazardous Energy (Lockout/Tagout) -- Electrical Occupational Safety and Health Standards -- Summary -- ch. 4 Lockout, Tagging, and the Control of Hazardous Energy -- Introduction -- The Occupational Safety and Health Act of 1970 -- Safety and Health Regulations for Construction -- General Safety and Health Provisions -- Electrical Safety Requirements -- Occupational Safety and Health Standards -- Lockout and Tagging -- The Control of Hazardous Energy (Lockout/Tagout) -- Typical Minimal Lockout Procedures -- Definitions -- Achieving an Electrically Safe Work Condition -- The Process of Achieving an Electrically Safe Work Condition -- Verifying an Electrically Safe Work Condition -- Summary -- ch. 5 Introduction to NFPA 70E -- Introduction -- NFPA 70E History, Introduction, and Application of Safety-Related Work Practices -- History and Evolution of NFPA 70E -- NFPA 70E Introductory Information -- Purpose and Scope -- Organization and Arrangement -- Rules, Explanatory Material, and Formal Interpretations -- NFPA 70E Definitions -- Application of Safety-Related Work Practices -- General Requirements for Electrical Safety-Related Work Practices -- Host and Contract Employer Responsibilities -- Training Requirements -- Electrical Safety Program -- Use of Equipment -- Underground Electrical Lines and Equipment -- Establishing an Electrically Safe Work Condition -- Work Involving Electrical Hazards -- Additional Considerations -- Summary -- ch. 6 Justification, Assessment, and Implementation of Energized Work -- Introduction -- Application, Justification, and Documentation -- General -- Electrically Safe Working Conditions -- Energized Work -- Energized Electrical Work Permit -- Working While Exposed to Electrical Hazards -- Approach Boundaries -- Shock Hazard Analysis -- Shock Protection Boundaries -- Approach to Exposed Energized Electrical Conductors or Circuit Parts Operating at 50 Volts or More -- Approach by Unqualified Persons -- Arc Flash Hazard Analysis -- Arc Flash Boundary -- Protective Clothing and Other Personal Protective Equipment -- Equipment Labeling -- Other Precautions for Personnel Activities -- Personal and Other Protective Equipment -- Personal Protective Equipment (PPE) -- Other Protective Equipment -- Standards for Other Protective Equipment -- Alerting Techniques -- Work on Overhead Lines -- Summary -- ch. 7 Incident Energy Varies by Fault Current Magnitude and Duration -- Introduction -- Short-Circuit Current -- Bolted Short-Circuit (Fault) Currents -- Arcing Faults -- OCPD Clearing Time -- Reading OCPD Time-Current Curves -- Fuse Clearing Times -- Current-Limiting Fuse Clearing Times -- Circuit Breaker Clearing Times -- Generalized OCPD Clearing Times -- OCPD Condition of Maintenance's Effects on Clearing Time -- Ramifications of OCPD Clearing Times -- OCPD Incident Energy Profiles -- Circuit Breaker Incident Energy Profiles -- Fuse Incident Energy Profiles -- Summary -- ch. 8 Arc Flash Hazard Analysis Methods -- Introduction -- Common AFHA Methods Summary Tables -- HRC Method -- HRC Method for AC Systems -- HRC Method for DC Systems -- AFB and Incident Energy Calculation Methods Discussion -- IEEE 1584 AFHA Calculation Methods and Tools -- Other AFHA Calculation Methods -- Other Considerations -- Updating AFHA -- Arcing Currents in the Long Time Characteristic of Overcurrent Protective Devices -- Overcurrent Protective Device Condition of Maintenance -- Documentation -- Labeling -- Overcurrent Protective Device to Use for AFHA -- Arc Blast Considerations -- Summary -- ch. 9 Fundamentals of 3-Phase Bolted Fault Currents -- Introduction -- Short-Circuit Calculation Requirements -- Short-Circuit Current Calculation Basics -- Sources of Short-Circuit Current -- Short-Circuit Current Factors -- Effects of Generators and Motors on Short-Circuit Current -- Effect of Transformers on Short-Circuit Current -- Effect of Conductors on Short-Circuit Current -- Effect of Short-Circuit Current on Arc-Flash Hazards -- Switching Scenarios -- Power Source Scenarios -- Motor Contribution Scenarios -- Effect of System Changes on Arc-Flash Hazard -- Procedures and Methods -- Point-to-Point Method -- 3-Phase Short-Circuit Current Calculation Procedure -- Point-to-Point Method Examples -- Short-Circuit Calculation Software Programs -- Summary -- ch. 10 OCPD Work Practices and Maintenance Considerations -- Introduction -- Overcurrent Protective Device Work Practices -- Resetting Circuit Breakers or Replacing Fuses -- Circuit Breakers -- Fuses -- Maintenance: How It Relates to Electrical Safety -- How a Lack of Maintenance Can Increase Hazards -- Lack of Lubrication -- Maintenance Can Affect Safety -- General Maintenance Requirements -- Maintenance Programs and Frequency of Maintenance -- Maintenance and Hazard Identification/Risk-Assessment -- Qualifications for Performing Maintenance on Electrical Equipment -- Legal Repercussions -- Safe Versus Unsafe Example -- Lack of Maintenance Example -- Summary -- ch. 11 Electrical System Design and Upgrade Considerations -- Introduction -- Overcurrent Protective Device-Considerations -- Non-Current-Limiting Overcurrent Protective Devices -- Current-Limiting Overcurrent Protective Devices -- Overcurrent Protective Devices Life Cycle Consistency -- Consideration for Fusible Systems -- Circuit Breakers -- Relaying Schemes -- Separate Enclosure for Main Disconnect -- Specify a Main on Each Service -- High-Speed Fuse Assembly -- Sizing Underutilized Circuits with Lower-Ampere-Rated Fuses or Circuit Breakers -- Evaluating OCPDs in Existing Facilities for Interrupting Rating -- "No Damage" Protection for Motor Controllers -- Selective Coordination -- Additional Design for Safety-Considerations -- Remote Monitoring -- Finger-Safe Products and Terminal Covers -- Isolating the Circuit: Installation of an "In-Sight" Disconnect for Each Motor -- Breaking up Large Circuits into Smaller Circuits -- Remote Opening and Closing -- Arc-Resistant (Arc-Diverting) Medium-Voltage Switchgear -- Resistance-Grounded Systems -- Arc Initiator/Absorber Box -- Summary.
Includes bibliographical references.
Keywords: ELECTRICAL ENGINEERING -- SAFETY MEASURES